PERLINDUNGAN HUKUM TERHADAP KAUM DIFABEL KORBAN PEMERKOSAAN - Alfian, Alfan (FIAT JUSTISIA, 2015)
In Indonesia arrangement on Human Rights has been included in the constitution, starting from Article 28A to 28J, even re-clarified in Article 29 of the Constitution of 1945. Viewing of the formulation of articles in the 1945 Constitution, suggests that there is injury history so deep against human rights enforcement in Indonesia before the reform, thus setting Human Rights was included as detailed in the constitution that should only set the rules subject. Associated with the handling of victims with disabilities before the law, into a constitutional basis that disabled people should be applied equally before the law, even if not physically perfect and different from normal people as usual. Protection against disabilities, actually are not discussed explicitly in the constitution, but the Legal Power is in our constitution has leads to there, so some sectorial laws need to be explain to specifically.Keywords: Legal Protection , Disability , Rape